Uterine Leiomyoma with Massive Lymphoid Infiltrate in a Patient with History of Assisted In-Vitro Fertilization - Monia DI PRETE; Matteo COLLAMARINI; Claudio COLLAMARINI; Francesco SESTI; Alessandro MAURIELLO; Giampiero PALMIERI (Federation of Turkish Pathology Societies, 2020)
Uterine leiomyomas are the most common benign tumors of the gynecological tract. Massive lymphocytic infiltration has been reported rarely in uterine leiomyomas and it has been described as a pathogenetic correlation with gonadotropin-releasing hormone agonists. Uterine leiomyomas with massive lymphoid infiltration have to be differentiated from non-Hodgkin lymphomas. We report a case of a woman without a history of gonadotropin-releasing hormone agonist treatment, who presented with a uterine leiomyoma that increased in size after the procedure of assisted in-vitro fertilization, and associated with massive nodular lymphoid infiltrate simulating, morphologically, a non-Hodgkin lymphoma. Uterine leiomyoma with massive lymphocytic infiltration is a very rare entity, probably of reactive significance, which has to be differentiated from diseases that need a systemic therapeutic approach.